PENENTUAN KUALITAS PELUMASAN MESIN - Fajar, Rizqon; Yubaidah, Siti (MESIN, 2007)
The monitoring on commercial engine lubricants have resulted that the properties ofmost lubricants (synthetic, semi synthetic and mineral type) have met the requirements specifiedforcommon engine oil. However, significant variations have been found in the properties such asviscosity, viscosity index and additive contents (anti oxidant &detergent). Too high in viscosity willgive difficulty during engine staring and increases the fuel consumption. Meanwhile if the viscosity istoo low this will create more risks for engine damage (metal to metal contact). Some of the samplesfrom synthetic, semi synthetic and mineral lubricants have shown that the additives contents (antioxidant, antiwear anddetergent) are too low. Lower additive contents means that the service life ofthelubricants will be shorter than the usual recommendation. Most of mineral lubricants are too highviscosity at normal temperature of engine operation (lOffC). This will decrease the efficiencyfor theengine operations (highfuel consumption).